The Contribution of Agility, Balance, and Foot-Eye Coordination to the Ability to Dribble the Ball in Football Games for Students at SMA Negeri 3 Pinrang - Sabir, Muh. Akbar; Bismar, Ahmad Rum; Ishak, Muhammad (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This research aims to determine: the contribution of agility, balance and eye-foot coordination to students' ability to dribble the ball in football games. This research is a type of regression research. The population of this study were all students of SMA Negeri 3 Pinrang with a total research sample of 30 students selected by random sampling. The data analysis techniques used are descriptive, data normality and regression using the SPSS Version 21.00 system at a significance level of 95% or α0.05. Based on the results of data analysis, this research concludes that: (1) Agility has a significant contribution to the ability to dribble the ball in football games among students at SMA Negeri 3 Pinrang, amounting to 45.8%; (2) Balance has a significant contribution to the ability to dribble the ball in the game of football among students at SMA Negeri 3 Pinrang, amounting to 63%; (3) Eye-foot coordination has a significant contribution to the ability to dribble the ball in a football game among students at SMA Negeri 3 Pinrang, amounting to 58.4%; and (4) Agility, balance and eye-foot coordination have a significant contribution to the ability to dribble the ball in the game of football among students at SMA Negeri 3 Pinrang, amounting to 79.6%.